Local content requirements : perspectives under WTO law and other international norms - Spadano, Lucas Eduardo Freitas do Amaral (2020)
Local content requirements (LCRs) are traditionally described as industrial policy measures requiring the use of a certain amount or value of national parts or components in the manufacturing of finished goods. Conventional wisdom holds that they are clearly prohibited by international trade and investment disciplines, as evidenced by consistent case law. Yet, LCRs continue to be pervasively used by many countries. The thesis challenges conventional wisdom by looking into the referred rules and how they impact controversial policy areas, especially subsidies to \"localise\" manufacturing activities, of the types that were challenged in two WTO disputes that are studies in detail: the United States - Tax Incentives and Brazil - Taxation cases. The thesis confirms a threefold proposition: (i) many LCRs are lawful under international law, notably in the area of services and government procurement; (ii) various prohibited LCRs are tolerated in certain areas, such as mineral resource concessions and official credit facilities; and (iii) case law on LCRs is only partially consistent, as far as the national treatment obligation is concerned. By contrast, the disciplines on \"local content\" subsidies and \"localisation\" incentives, as recently interpreted in the two cases studied, are rather unclear and perplexing. In order to improve the security and predictability of the policy space available for such measures, the thesis suggests a reform or a reinterpretation of the rules.